The 2008 financial crisis and taxation policy - Hemmelgarn, Thomas; Nicodeme, Gaetan (Munich, 2010)
"The 2008 financial crisis is the worst economic crisis since the Great Depression of 1929. It has been characterised by a housing bubble in a context of rapid credit expansion, high risk-taking and exacerbated financial leverage, leading to deleveraging and credit crunch when the bubble burst. This paper discusses the interactions between tax policy and the financial crisis. In particular, it reviews the existing evidence on the links between taxes and many characteristics of the crisis. Finally, it examines some possible future tax options to prevent such crises."